Trançando vidas: entre frestas e tessituras de cuidado para a sustentabilidade da vida - Santos, Tainá Souza (2024)
This research aims to highlight the experiences and alliances between black and peripheral women linked to a Civil Society Organization (CSO) located in the city of São Carlos - SP. The CSO Casa da Infância Estrela da Manhã is an institution that offers projects and assistance to families, children and young people in a context of social vulnerability in the Antenor Garcia neighborhood. Among the projects offered by the institution is Trançando Vidas, which welcomes women from the community with the aim of preventing domestic violence, promoting financial autonomy, strengthening bonds and meeting family demands through social assistance services. Based on ethnographic research in Estrela da Manhã, , the purpose of this work is to describe the production of care among women for the sustainability of personal and family life, drawing on theoretical references from black and decolonial feminism, as well as to point to the recent discussions at national level about care work for the elaboration of the National Care Plan and Policy.